Characteristics of Patients with Acute Respiratory Infections Using Antibiotics at Hospital X - Haryani, Mega; Sormin, Ida Paulina; Liandhajani, Liandhajani (Journal La Medihealtico, 2024)
Infection channel Respiratory acute (ARI) includes a number involving infections various part channel breath, of nose and throat until bronchi and lungs. Use antibiotics often required For treat ARI, though approach prevention like promotion cleanliness hands, management environment, and education society is also very important. Factors like type gender, age, education, occupation, marital status, and smoking status join in role in increase risk affected by ISPA. Study This aim For identify characteristics patients suffering from ARI with various aspect covers type gender, range age, level education, type employment, marital status, and smoking status. Study This use design descriptive observational that utilizes secondary data from notes document medical ARI patients at the center record Hospital. Total samples observed in study This is as many as 110 patients. Analysis show domination patient women (56.3%), which is possible influenced by factors biological, hormonal, and social. Age patients at Hospital X are dominated by groups age 18-30 years (50%), which is likely big influenced by style life and activities population on a range age This. Majority patient in study This own education undergraduate level (33.6%). Patients with work as employee private reached 30%, meanwhile percentage patients who smoke reached 54.5%, which shows significant prevalence in population This. In research This, of the total 110 patients at Hospital X, the majority is Woman. Group age the most is 18-30 years old, which is often active in a way social and productive. By education, in part big patient own background behind education high.